Hand Mirror Cells and Hypercalcemia: A Rare Presentation of Pediatric Acute Lymphoblastic Leukemia. Issue 3 (April 2020) - Cacciotti, Chantel; Leber, Brian; Cox, Stephanie; Arredondo, Jorge; Bassilious, Ereny; Athale, Uma
Abstract : Hand mirror cell (HMC) leukemia is a variant of acute lymphoblastic leukemia previously described in the adult population where lymphoblasts manifest distinctive hand mirror morphologic features. HMC has been previously identified in 23% of childhood acute lymphoblastic leukemia patients, but its prognostic significance in children is not well understood. Hypercalcemia is also uncommon in childhood leukemias. Hypercalcemia associated with HMC leukemia has not been previously reported. We report a 5-year-old boy with HMC B-lymphoblastic leukemia who presented with hypercalcemia.